# Use Definition To Find Derivative H Formula, Use Definition To Find Derivative

## 6.2 Differentiation from first principles (EMCH6)

We know that the gradient of the tangent to a curve with equation (y = f(x)) at (x=a) can be determine using the formula:

< ext{Gradient at a point } = lim_{h o 0}frac{fleft(a+h ight)-fleft(a ight)}{h}>

We can use this formula to determine an expression that describes the gradient of the graph (or the gradient of the tangent to the graph) at any point on the graph. This expression (or gradient function) is called the derivative.

Đang xem: Derivative h formula

Derivative

The derivative of a function (fleft(x
ight)) is written as ({f}”left(x
ight)) and is defined by:

<{f}"left(x ight)=lim_{h o 0}frac{fleft(x+h ight)-fleft(x ight)}{h}> Differentiation

The process of determining the derivative of a given function.

This method is called differentiation from first principles or using the definition.

## Worked example 7: Differentiation from first principles

### Write down the formula for finding the derivative using first principles

<{g}"left(x ight)=lim_{h o 0}frac{gleft(x+h ight)-gleft(x ight)}{h}>

### Determine (gleft(x+h ight))

egin{align*} g(x) &= 2x – 3 \ & \ gleft(x+h
ight) &= 2left(x+h
ight) – 3 \ &= 2x + 2h – 3 end{align*}

### Substitute into the formula and simplify

egin{align*} {g}”left(x
ight) & = lim_{h o 0}frac{2x + 2h – 3 -left(2x – 3
ight)}{h} \ & = lim_{h o 0}frac{2h}{h} \ & = lim_{h o 0} 2 \ & = 2 end{align*}

Notation

There are a few different notations used to refer to derivatives. It is very important that you learn to identify these different ways of denoting the derivative and that you are consistent in your usage of them when answering questions.

See also  What Is The Derivative Formula Of U/V Derivative Formula, {Displaystyle {Begin{Aligned}{Frac {D(Uv)}{Dx

If we use the common notation (y=fleft(x
ight)), where the dependent variable is (y) and the independent variable is (x), then some alternative notations for the derivative are as follows:

<{f}"left(x ight)={y}"=frac{dy}{dx}=frac{df}{dx}=frac{d}{dx}=Dfleft(x
ight)={D}_{x}y>

The symbols (D) and (frac{d}{dx}) are called differential operators because they indicate the operation of differentiation.

(frac{dy}{dx}) means (y) differentiated with respect to (x). Similarly, (frac{dp}{dx}) means (p) differentiated with respect to (x).

Important: (frac{dy}{dx}) is not a fraction and does not mean (dy div dx).

Video: 28W2

## Worked example 8: Differentiation from first principles

Find the derivative of (fleft(x
ight)=4x^{3}) from first principles.Determine ({f}” ( ext{0,5})) and interpret the answer.

### Write down the formula for finding the derivative from first principles

<{f}"left(x ight)=lim_{h o 0}frac{fleft(x+h ight)-fleft(x ight)}{h}>

### Substitute into the formula and simplify

egin{align*} {f}”left(x
ight) & = lim_{h o 0}frac{4left(x + h
ight)^{3} – 4x^{3}}{h} \ & = lim_{h o 0}frac{4left(x^{3} + 3x^{2}h + 3xh^{2} + h^{3}
ight) – 4x^{3}}{h} \ & = lim_{h o 0}frac{4x^{3} + 12x^{2}h + 12xh^{2} + 4h^{3} – 4x^{3}}{h} \ & = lim_{h o 0}frac{12x^{2}h + 12xh^{2} + 4h^{3}}{h} \ & = lim_{h o 0}frac{h left(12x^{2} + 12xh + 4h^{2}
ight)}{h} \ & = lim_{h o 0} (12x^{2} + 12xh + 4h^{2}) \ & = 12x^{2} end{align*}

### Calculate ({f}” ( ext{0,5})) and interpret the answer

egin{align*} {f}”left(x
ight) & = 12x^{2} \ herefore {f}”left( ext{0,5}
ight) & = 12( ext{0,5})^{2} \ &= 12left( frac{1}{4}
ight) \ &= 3 end{align*}The derivative of (f(x)) at (x = ext{0,5}) is ( ext{3}).The gradient of the function (f) at (x = ext{0,5}) is equal to ( ext{3}).The gradient of the tangent to (f(x)) at (x = ext{0,5}) is equal to ( ext{3}).

### Substitute into the formula and simplify

egin{align*} frac{dp}{dx} & = lim_{h o 0}frac{-frac{2}{x + h} -left(- frac{2}{x}
ight)}{h} end{align*}

It is sometimes easier to write the right-hand side of the equation as:

egin{align*} frac{dp}{dx} & = lim_{h o 0}frac{1}{h} left(frac{-2}{x + h} + frac{2}{x}
ight) \ & = lim_{h o 0} frac{1}{h} left(frac{-2x + 2(x + h)}{x(x + h)}
ight) \ & = lim_{h o 0} frac{1}{h} left(frac{-2x + 2x + 2h }{x(x + h)}
ight) \ & = lim_{h o 0} frac{1}{h} left(frac{2h }{x^{2} + xh}
ight) \ & = lim_{h o 0} frac{2}{x^{2} + xh} \ & = frac{2}{x^{2}} end{align*}

Notice: even though (h) remains in the denominator, we can take the limit since it does not result in division by ( ext{0}).

## Worked example 10: Differentiation from first principles

Differentiate (gleft(x
ight)= frac{1}{4}) from first principles and interpret the answer.

### Write down the formula for finding the derivative from first principles

<{g}"left(x ight)=lim_{h o 0}frac{gleft(x+h ight)-gleft(x ight)}{h}>

### Substitute into the formula and simplify

egin{align*} {g}”left(x
ight) & = lim_{h o 0}frac{ frac{1}{4} – frac{1}{4}}{h} \ & = lim_{h o 0}frac{0}{h} \ & = lim_{h o 0} 0 \ & = 0 end{align*}

The gradient of (g(x)) is equal to ( ext{0}) at any point on the graph. The derivative of this constant function is equal to ( ext{0}).

See also  A Gentle Introduction To Function Derivative Function, Rules Of Calculus

Test yourself now

High marks in maths are the key to your success and future plans. Test yourself and learn more on wnyrails.org Practice.

See more articles in category: Derivative